The Invasion of Ukraine from the Point of View of the European Court of Human Rights: Extraterritorial Responsibility of Russia and (Un)Control of International Humanitarian Law - Salinas Alcega, Sergio (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2023)
The negative impact of the invasion of Ukraine by Russia on international law has many dimensions, the massive and flagrant violation of human rights being one of the most relevant. From this perspective, the role of international mechanisms for the protection of these rights, and notably the European Convention system and the European Court of Human Rights (ECtHR), has become particularly important. The Strasbourg Court’s approach can be divided into two different aspects, which are obviously interrelated. The main aspect relates to the scope of the European Convention on Human Rights’ (ECHR) responsibility regarding Russia. Considering that relevant acts are committed by Russia outside its territory, the question of the extraterritorial application of the Convention becomes crucial. The second aspect relates to how the Strasbourg judges see the interplay between the ECHR and international humanitarian law, and especially their role in exercising a certain amount of control over the latter’s application. Here, the Court could help remedy the shortcomings that currently exist in terms of the availability of specific mechanisms to demand responsibility from the States for the violation of norms in this domain of international law. Regarding both aspects, there is already a rich and developing Strasbourg jurisprudence even if, of course, it is not exempt from criticism. The acts committed by Russia in Ukraine may make it possible to revisit this jurisprudence and allow it to overcome certain shortcomings which have been identified.